Analisis Rasio Keuangan Pada Pertumbuhan Laba Perusahaan Manufaktur Sub Sektor Food & Baverages Yang Terdaftar Di IDX - Moh. Zaki Kurniawan (Universitas Islam Balitar, 2022)
Profit is one of the goals of the company in running a businees. The existence of profits that grow and develop from the company is one indicator for companies that are in good performance. Documentation and observation methods were chosen for secondary data collection techniques. This study gives partial and simultaneous result that the current ratio, net profit margin, total asset turnover and dept to equity ratio have no effect on profit growth in the food & beverage sub-sector